Interference of heart and transcutaneous oxygen monitoring in the measurement of bioelectrical impedance analysis in preterm newborns - Viviane C. Comym; Yuri S. Macedu; Eduardo K.P.B. Neves; Arnaldo C. Bueno; Herminia C. Fernandez; Maria E.L. Moreira; Alan A. Vieira (Brazilian Society of Pediatrics, 2016)
Objective: To verify if the connection between electrodes for heart and transcutaneous oxygen monitoring interfere with the measurement of electrical bioimpedance in preterm newborns. Methods: This was a prospective, blinded, controlled, cross‐sectional, crossover study that assessed and compared paired measures of resistance (R) and reactance (Xc) by BIA, obtained with and without monitoring wires attached to the preterm newborn. The measurements were performed in immediate sequence, after randomization to the presence or absence of electrodes. The sample size calculated was 114 measurements or tests with monitoring wires and 114 without monitoring wires, was calculated for a difference between the averages of 0.1 ohms, with an alpha error of 10% and beta error of 20%, with significance < 0.05. Results: No differences were observed between the R (677.37 ± 196.07 vs. 677.46 ± 194.86) and Xc (31.15 ± 9.36 vs. 31.01 ± 9.56) values obtained with and without monitoring wires, respectively, with good correlation between them (R: 0.997 and Xc: 0.968). Conclusion: The presence of heart and/or transcutaneous oxygen monitoring wires connected to the preterm newborn did not affect the values of R or Xc measured by BIA, allowing them to be carried out in this population without risks.